Economic Assessment of Mobilized Thermal Energy Storage for Distributed Users: A Case Study in China. (June 2016) - Guo, Shaopeng; Zhao, Jun; Yan, Jinyue; Jin, Guang; Wang, Xiaotong
Abstract: Mobilized thermal energy storage (M-TES) system can be an alternative of the conventional heating system to meet the heat demand for distributed users. This paper conducted a case study of the M-TES system in China. The operating strategies (OS) of the M-TES with different transportation schemes were compared. Moreover, the economic assessment was performed based on the project's net present value (NPV) and payback period (PBP). The OS with 6 trips per day is the most profitable with pay-back time of about 2, 3 and 5 years if the waste heat costs at the level of 0 €/MWh, 3300 €/MWh, and 6600 €/MWh, respectively.